On the hippie trail : Istanbul to Kathmandu and the making of a travel writer - Steves, Rick, 1955- (Avalon Travel, 2025)
Stow away with Rick Steves for a glimpse into the unforgettable moments, misadventures, and memories of his 1978 journey on the legendary Hippie Trail.